FRI0205 Clues to systemic sclerosis sine scleroderma. (1st June 2001) - Rosner, I; Slobodin, G; Rozenbaum, M; Naschitz, JE; Toubi, E; Kessel, A; Yeshurun, D
Abstract : Background: There is substantial difficulty in the diagnosis of progressive systemic sclerosis where visceral involvement precedes cutaneous expression of the disease. Objectives: To describe clues to the diagnosis of progressive systemic sclerosis sine scleroderma (ssSSc). Methods: Report of 3 cases and review of the MEDLINE database concerning ssSSc. Results: Tweny five patients from the literature and 3 from our unit fulfilled the inclusion criteria, 13 females and 15 males, mean age 51.2(SD17.2) years. Conditions motivating the search for ssSSc were pulmonary fibrosis (44%), congestive heart failure (19%), esophageal dysfunction (7%), malabsorption (11%), nephropathy (11%), fever of unknown origin (3.5%) and seizures (3.5%). An overt undifferentiated connective tissue disease was present in 7 pts. Multisystem involvement became apparent when carefully searched for in all but one patient. ANA and RF were found in 13 of 17 and "scleroderma pattern" was noted in 9 of 13 patients on nailfold capillaroscopy. Taut skin developed later in 57% of pts following extracutaneous presentation by 1 month to 7 yrs (mean 2.3 yrs). Conclusion: Clues to the diagnosis of ssSSc can be classified as: 1) background conditions – unclassified system disorder, Raynaud's, polyarthritis 2) evolving visceropathy of obscure provenience – dysphagia, malabsoption, pulmonary fibrosis, heart failure, nephropathy 3) corroborative laboratory and clinical features – hyper/hypopigmentation, telangiectasis, calcinosis, typical nailfold capillaroscopy 4) confirmatory evidence – visceral biopsy, appearance of taut skin.